Urgensi Minat Baca Peserta Didik terhadap Kemampuan Literasi dan Numerasi di UPT SD Negeri 3 Gresik (Indo-MathEdu Intellectuals Journal, 2024)
This study examines the urgency of students' reading interest in literacy and numeracy skills at UPT SD Negeri 3 Gresik. The method used in this study is qualitative with a descriptive type. Subject determination is carried out using purposive sampling, which is a technique of determining the subject using certain criteria. Data collection techniques in this study are by observation, questionnaires, and interviews. The data collected came from related respondents/subjects who aimed to get an idea of the focus of the problem in this study. Questionnaires are distributed online so that students can work on questionnaires with flexible time with a predetermined period. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusions. The results of data analysis show that interest in reading is very important for the development of students' literacy and numeracy skills. Without a high interest in reading, students will automatically experience obstacles to the development of literacy and numeracy skills. Policy innovations created and carried out by the principal together with all teachers at UPT SD Negeri 3 Gresik in the form of habituation every week and the implementation of interesting teaching methods and media to build interest in reading to improve the literacy and numeracy skills of UPT SD Negeri 3 Gresik students.